(untitled) (Global Journal of Human-Social Science, 2023)
Revolution is not a finished concept It has a specific history and has mobilized great discussions over the centuries classical antiquity there has been debate about the best Constitution and the form of citizens However the term is potentially away from its original political conceptions that relates the word to its social ties so crucial in the theoretical structuring in the field of human sciences in addition to the mobilizations and experiences of individuals and societies Linked more to technological innovations or advertising campaigns revolution is increasingly distant from the meanings that monopolized investigations into the term in modernity After 18th century interpretations have been divided into two main branches one related to the liberal revolutions American 1776 and French 1789 the other attached to the Marxist tradition and the Russian process 1917 1 Perhaps as Trist n and Barros said Castro s death in 2016 it was a biological end of events and ideologies that marked the History of the last great political and social revolutions of recent centuries without which no other could be thought and articulated 2